1985
DOI: 10.1007/bf02123230
|View full text |Cite
|
Sign up to set email alerts
|

Immunological relationships betweenSalmonella flagella and their potential application for salmonellae detection by immunoassay

Abstract: Native flagella of ten Salmonella serotypes were shown to possess serotype-specific antigenic determinants as well as a multiple of common antigenic determinants, which varied in concentration. Each common antigenic determinant was shared by certain, but not all, serotypes. This has been demonstrated from agglutination and radioimmunometric assay (RIMA) results, using ten antisera raised in rabbits against purified polymeric flagellins from ten Salmonella serotypes as immunogens. The minimum detectable populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…ELISA of this antiserum after absorption with heterologous flagella suggested that, as is the case with Salmonella flagella (14), a proportion of these surface-exposed epitopes were crossreactive. The immunodominant surface-exposed Campylobacter flagellin epitopes were, however, serospecific and readily demonstrated by immunoprecipitation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…ELISA of this antiserum after absorption with heterologous flagella suggested that, as is the case with Salmonella flagella (14), a proportion of these surface-exposed epitopes were crossreactive. The immunodominant surface-exposed Campylobacter flagellin epitopes were, however, serospecific and readily demonstrated by immunoprecipitation.…”
Section: Discussionmentioning
confidence: 90%
“…Trust, unpublished data). Conformational epitopes also play a major role in the serospecificity of Salmonella flagella (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…A sensibilidade dos anti-soros testados neste trabalho foi concordante com a observada em vários outros trabalhos realizados com diferentes técnicas imunoenzimáticas e sorotipos de Salmonella [15,20,21,26]. Nestes estudos, a sensibilidade do teste imunoenzimático variou de 10 2 a 10 6 UFC/mL.…”
Section: Tabela 1 Desempenho Do Teste Imunoenzimático Na Detecçãounclassified
“…In the case of H antigen, preparation of specific antiserum was facilitated by the use of purified flagellin for immunization, although the presence of conserved regions in the molecule among different serovars originated possible cross-reactions depending on the procedure used for antiserum generation [25,26]. Upon the widespread use of techniques for Monoclonal Antibody (MAb) generation, several MAbs for strain serotyping have been described [27,28].…”
Section: Introductionmentioning
confidence: 99%